Relationship between energy balance and reward system gene polymorphisms and appetitive traits in young Mexican subjects - Rivera-Iñiguez, Ingrid; Hunot-Alexander, Claudia; Sepúlveda-Villegas, Maricruz; Campos-Medina, Liliana; Roman, Sonia (Frontiers in Nutrition, 2024)
Introduction: Appetitive traits are influenced by the interplay between genetic and environmental factors. This study aimed to explore the relationship between gene polymorphisms involved in the regulation of energy balance and food reward and appetitive traits in young Mexican subjects.This cross-sectional study involved 118 university freshman undergraduates who completed the Adult Eating Behaviour Questionnaire for Spanish speakers (AEBQ-Esp) to assess their appetitive traits. A real-time PCR system was employed to determine gene polymorphisms involved in energy balance (LEP rs7799039, MC4R rs17782313, FTO rs9939609, GHRL rs696217), and reward system (DRD2/ANKK1 Taq1A rs1800497 and COMT rs4680).The mean age of participants was 20.14 ± 3.95 years, 71.2% were women and their mean BMI was 23.52 ± 4.05 kg/m 2 . COMT Met allele carriers presented a significantly higher "Emotional overeating" mean score than Val allele carriers (2.63 ± 0.70 vs. 2.23 ± 0.70, p = 0.028). The MC4R CC+CT genotype correlated positively with "Emotional overeating" (Phi = 0.308, p = 0.01). The COMT MetMet+MetVal genotype correlated with higher "Emotional overeating" (r = 0.257, p = 0.028; Phi=0.249, p = 0.033). The protective genotype FTO TT correlated positively with "Emotional undereating" (Phi =0.298, p = 0.012). Carriers of the risk genotype MC4R CC+CT presented a higher risk of "Emotional overeating" than TT carriers (OR=2.4, 95% CI 1.3-4.8, p = 0.034). Carriers of the risk genotype COMT MetMet+MetVal (OR=3.4, 95% CI 1.1-10.3, p = 0.033), were associated with a higher risk of "Emotional overeating" than ValVal carriers. The protective genotype TT from FTO was associated with "Emotional undereating" (OR=1.8, 95% CI 1.1-9.1, p = 0.014).The study found a relationship between the protective genotypes of FTO TT and "Emotional undereating" and risk genotypes of COMT Met/Met+Met/Val and MC4R CC+CT with "Emotional overeating". These genetic factors may increase weight gain by enhancing hedonic food consumption and reducing satiety control. Future studies should focus on replication studies in ethnically diverse young adults and life stages to explore the relationship between polymorphisms and appetitive traits and weight. This will help tailor personalized nutrigenetic strategies to counteract disordered eating patterns leading to obesity and associated co-morbidities.